Cured liquid crystal film, optical film including the cured liquid crystal film, and display device

By using a liquid crystal cured film composed of a polymerizable liquid crystal compound and a specific photocuring agent, the problem of the reduction of the phase difference value of the traditional liquid crystal cured film in a high temperature environment is solved, and the performance stability and efficiency are achieved.

JP7649895B2Active Publication Date: 2025-03-21SUMITOMO CHEM CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2024031481
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2015-07-24
Filing Date
2024-03-01
Publication Date
2025-03-21
Estimated Expiration
2036-07-25

AI Technical Summary

Technical Problem

The phase difference value of the traditional liquid crystal cured film will decrease in high temperature environments, resulting in a degradation in performance.

Method used

A liquid crystal cured film made of polymerizable liquid crystal compounds is used, with a maximum absorption wavelength between 300 nm and 380 nm, and the correct direction and degree of polymerization of liquid crystal molecules are ensured through specific photocuring agent composition and photocuring conditions.

Benefits of technology

The liquid crystal cured film has a reduced degree of phase difference value in a high temperature environment, and maintains a high performance stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649895000001
    Figure 0007649895000001
  • Figure 0007649895000002
    Figure 0007649895000002
  • Figure 0007649895000003
    Figure 0007649895000003
Patent Text Reader

Abstract

To provide a liquid crystal cured film that can reduce the amount of reduction in phase difference value when exposed to a high-temperature environment.SOLUTION: A liquid crystal cured film obtained by polymerizing a polymerizable liquid crystal compound has a maximum absorption wavelength in a range from 300 to 380 nm, and satisfies (1-P' / P0)×100≥73, wherein P' is smaller one of P values of two surfaces perpendicular to the thickness direction of the liquid crystal film, P0 is a P value of the polymerizable liquid crystal compound, the P value is represented by I(1) / I(2), I(1) is a peak intensity derived from in-plane deformation vibration of an ethylenically unsaturated bond in infrared total reflection absorption spectrum measurement, and I(2) is a peak intensity derived from stretching vibration of an unsaturated bond of an aromatic ring in the infrared total reflection absorption spectrum measurement.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cured liquid crystal film, an optical film including the cured liquid crystal film, and a display device. More specifically, the present invention relates to a cured liquid crystal film, an optical film including the cured liquid crystal film, a circular polarizer including the cured liquid crystal film or the optical film, and a display device including the circular polarizer. [Background technology]

[0002] In touch panel display devices such as flat panel displays (FPDs), members including optical films such as polarizing plates and retardation plates are used. As such optical films, optical films including a liquid crystal cured film formed from a liquid crystal cured film-forming composition including a polymerizable liquid crystal compound are known. Patent Document 1 describes an optical film including a liquid crystal cured film that exhibits reverse wavelength dispersion. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP2012-021068 (Published February 2, 2012) Summary of the Invention [Problem to be solved by the invention]

[0004] A liquid crystal cured film formed from a conventional liquid crystal cured film-forming composition has a problem in that its retardation value decreases when exposed to a high-temperature environment. [Means for solving the problem]

[0005] In order to solve the above problems, the present invention provides the following [1] to

[14] .

[0006] [1] A liquid crystal cured film obtained by polymerizing a polymerizable liquid crystal compound, The liquid crystal cured film has a maximum absorption wavelength in the range of 300 nm or more and 380 nm or less, A liquid crystal cured film satisfying formula (Y).

[0007] (1-P' / P0) x 100 ≧ 73 … (Y) (In the formula, P' represents the smaller P value of the two P values ​​on the plane perpendicular to the thickness direction of the liquid crystal cured film.

[0008] P0 represents the P value of the polymerizable liquid crystal compound.

[0009] The P value is expressed as I(1) / I(2).

[0010] I(1) represents the peak intensity due to the in-plane bending vibration of the ethylenically unsaturated bond as determined by infrared total reflection absorption spectroscopy, and I(2) represents the peak intensity due to the stretching vibration of the unsaturated bond of the aromatic ring as determined by infrared total reflection absorption spectroscopy. [2] The liquid crystal cured film according to [1], which satisfies formula (3).

[0011] 100nm <Re(550)<160nm …(3) (In the formula, Re(550) represents an in-plane retardation value for light having a wavelength of 550 nm.) [3] The liquid crystal cured film according to [1], which satisfies formula (1) and formula (2).

[0012] Re(450) / Re(550)≦1.00 …(1) 1.00≦Re(650) / Re(550) …(2) (In the formula, Re(450) represents an in-plane retardation value for light with a wavelength of 450 nm, Re(550) represents an in-plane retardation value for light with a wavelength of 550 nm, and Re(650) represents an in-plane retardation value for light with a wavelength of 650 nm.) [4] Maximum absorption wavelength λ of polymerizable liquid crystal compound max (LC) 300nm≦λ max (LC)≦380nm The liquid crystal cured film according to [1], which satisfies the above.

[0013] [5] The liquid crystal cured film according to [1], further comprising a photopolymerization initiator composition.

[0014] [6] The liquid crystal cured film according to [5], wherein the photopolymerization initiator composition has an absorption maximum wavelength λ(A) and an absorption maximum wavelength λ(B), and these absorption maximum wavelengths λ(A) and λ(B) satisfy λ(A)<λ(B).

[0015] [7] The maximum absorption wavelength of the photopolymerization initiator composition and the maximum absorption wavelength λ of the polymerizable liquid crystal compound max (LC) 20nm<λ(B)-λ max (LC) or 20nm<λ max (LC)-λ(A) The liquid crystal cured film according to [6], which satisfies the above.

[0016] [8] The liquid crystal cured film according to any one of [5] to [7], comprising 1 to 20 parts by mass of the photopolymerization initiator composition relative to 100 parts by mass of the polymerizable liquid crystal compound.

[0017] [9] The liquid crystal cured film according to any one of [5] to [8], wherein the photopolymerization initiator composition contains a photopolymerization initiator having an oxime structure in the molecule.

[0018]

[10] The liquid crystal cured film according to any one of [1] to [9], obtained by curing a composition containing the polymerizable liquid crystal compound and a photopolymerization initiator composition.

[0019]

[11] The photopolymerization initiator composition has a maximum absorption wavelength λ(A) and a maximum absorption wavelength λ(B), These maximum absorption wavelengths λ(A) and λ(B) are λ(A)<λ(B) The liquid crystal cured film according to

[10] , which satisfies the above.

[0020]

[12] The maximum absorption wavelength of the photopolymerization initiator composition and the maximum absorption wavelength λ of the polymerizable liquid crystal compound. max (LC) 20nm<λ(B) -λmax (LC) or 20nm<λ max (LC)-λ(A) The liquid crystal cured film according to

[11] , which satisfies the above.

[0021]

[13] The liquid crystal cured film according to any one of

[10] to

[12] , comprising 1 to 20 parts by mass of the photopolymerization initiator composition relative to 100 parts by mass of the polymerizable liquid crystal compound.

[0022]

[14] The liquid crystal cured film according to any one of

[10] to

[13] , wherein the photopolymerization initiator composition contains a photopolymerization initiator having an oxime structure in the molecule.

[0023]

[15] An optical film comprising the cured liquid crystal film according to any one of [1] to

[14] .

[0024]

[16] A circular polarizing plate comprising the cured liquid crystal film according to any one of [1] to

[14] and a polarizing plate.

[0025]

[17] An organic electroluminescence display device comprising the liquid crystal cured film according to any one of [1] to

[14] .

[0026]

[18] A touch panel display device comprising the cured liquid crystal film according to any one of [1] to

[14] . Effect of the Invention

[0027] The liquid crystalline cured film according to the present invention has an effect of reducing the amount of decrease in retardation value when exposed to a high-temperature environment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] Hereinafter, an embodiment of the present invention will be described in detail. In this application, "A to B" means "A or more and B or less."

[0029] [Embodiment 1: Liquid crystal cured film] [Liquid crystal cured film] The present invention may provide a liquid crystal cured film obtained by polymerizing a polymerizable liquid crystal compound, having a maximum absorption wavelength in the range of 300 nm or more and 380 nm or less, and satisfying the following formula (Y): (1-P' / P0) x 100 ≧ 73 … (Y) (In the formula, P' represents the smaller P value of the two P values ​​on the plane perpendicular to the thickness direction of the liquid crystal cured film.

[0030] P0 represents the P value of the polymerizable liquid crystal compound.

[0031] The P value is expressed as I(1) / I(2).

[0032] I(1) represents the peak intensity due to the in-plane bending vibration of the ethylenically unsaturated bond as determined by infrared total reflection absorption spectroscopy, and I(2) represents the peak intensity due to the stretching vibration of the unsaturated bond of the aromatic ring as determined by infrared total reflection absorption spectroscopy. As shown above, the P value represents the ratio of the peak intensity (I(1)) derived from the in-plane bending vibration of the ethylenically unsaturated bond to the peak intensity (I(2)) derived from the stretching vibration of the unsaturated bond of the aromatic ring in the infrared total reflection absorption spectrum measurement. In the curing (polymerization) of the polymerizable liquid crystal compound, the unsaturated bond of the aromatic ring does not react, but the ethylenically unsaturated bond disappears. Therefore, the amount of ethylenically unsaturated bonds contained in the liquid crystal cured film can be calculated by determining the P value based on the peak intensity of the unsaturated bond of the unreacted aromatic ring as a relative standard. Therefore, the degree of polymerization in the liquid crystal cured film formed by polymerization of the polymerizable liquid crystal compound can be calculated using the formula (Y).

[0033] The value calculated by formula (Y) is 73 or more, preferably 83 or more. The value calculated by formula (Y) is preferably a high value within a range in which the retardation value does not decrease even when exposed to a high-temperature environment. The upper limit of the value calculated by formula (Y) may be, for example, less than 97, or may be 93 or less.

[0034] It is preferable that the value calculated by the formula (Y) is in the above-mentioned range, since the decrease (change) in the retardation value when the liquid crystal cured film is heated to a high temperature is reduced.

[0035] [Polymerizable liquid crystal compound] The polymerizable liquid crystal compound serving as the raw material of the liquid crystal cured film of the present invention has a maximum absorption wavelength λ max (LC) is a polymerizable liquid crystal compound having a wavelength of preferably 300 nm or more and 380 nm or less, more preferably 330 nm or more and 380 nm or less, and further preferably 330 nm or more and 360 nm or less.

[0036] The polymerizable liquid crystal compound is a compound having a polymerizable group and liquid crystallinity. The polymerizable group means a group involved in a polymerization reaction, and is preferably a photopolymerizable group. Here, the photopolymerizable group means a group that can be involved in a polymerization reaction by an active radical or an acid generated from a photopolymerization initiator.

[0037] Examples of photopolymerizable groups include vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxiranyl, and oxetanyl groups. Of these, vinyloxy, acryloyloxy, methacryloyloxy, oxiranyl, and oxetanyl groups are preferred, and acryloyloxy is more preferred. The liquid crystallinity may be thermotropic or lyotropic liquid crystal, but thermotropic liquid crystal is preferred in terms of the ability to precisely control the film thickness. In addition, the thermotropic liquid crystal may be nematic or smectic liquid crystal. The liquid crystallinity is preferably nematic in thermotropic liquid crystal from the viewpoint of ease of production.

[0038] As the polymerizable liquid crystal compound, those having a structure of the following formula (I) are particularly preferred in terms of expressing the above-mentioned reverse wavelength dispersion property.

[0039] LGD-Ar-DGL (I) In formula (I), Ar represents a substituted or unsubstituted divalent aromatic group. The aromatic group is a group having a planar ring structure, and the number of π electrons of the ring structure is [4n+2] according to the Huckel rule. Here, n represents an integer. When the ring structure contains heteroatoms such as -N= and -S-, the non-covalent bond electron pairs on these heteroatoms and the π electrons of the ring structure satisfy the Huckel rule, and the ring structure also includes aromaticity. The divalent aromatic group preferably contains at least one atom selected from the group consisting of a nitrogen atom, an oxygen atom, and a sulfur atom.

[0040] Each of the two Ds independently represents a single bond or a divalent linking group.

[0041] Two Gs each independently represent a divalent alicyclic hydrocarbon group.

[0042] Two Ls each independently represent a monovalent organic group, and at least one of them has a polymerizable group.

[0043] It is preferable that Ar has at least one selected from a substituted or unsubstituted aromatic hydrocarbon ring, a substituted or unsubstituted aromatic heterocycle, and an electron-withdrawing group. Examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, and an anthracene ring, and the like, and the benzene ring and the naphthalene ring are preferable. Examples of the aromatic heterocycle include a furan ring, a benzofuran ring, a pyrrole ring, an indole ring, a thiophene ring, a benzothiophene ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a triazole ring, a triazine ring, a pyrroline ring, an imidazole ring, a pyrazole ring, a thiazole ring, a benzothiazole ring, a thienothiazole ring, an oxazole ring, a benzoxazole ring, and a phenanthroline ring. Among them, it is preferable to have a thiazole ring, a benzothiazole ring, or a benzofuran ring, and it is more preferable to have a benzothiazole group. In addition, when Ar contains a nitrogen atom, it is preferable that the nitrogen atom has a π electron.

[0044] In formula (I), the total number of π electrons contained in the divalent aromatic group represented by Ar is N π is preferably 8 or more, more preferably 10 or more, even more preferably 14 or more, and particularly preferably 16 or more. Also, it is preferably 30 or less, more preferably 26 or less, and even more preferably 24 or less.

[0045] Examples of the aromatic group represented by Ar include the following groups.

[0046] [ka]

[0047] In formulas (Ar-1) to (Ar-22), * represents a linking portion, Z 0 , Z 1 and Z 2 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms.

[0048] Q 1 , Q 2 and Q 3 are each independently -CR 2’ R 3’ -, -S-, -NH-, -NR 2’ -, -CO- or -O-; R 2’ and R 3’ each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0049] J 1 , and J. 2 each independently represents a carbon atom or a nitrogen atom.

[0050] Y 1 , Y 2 and Y 3 each independently represents a substituted or unsubstituted aromatic hydrocarbon group or aromatic heterocyclic group.

[0051] W 1 and W 2 each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom; and m represents an integer of 0 to 6.

[0052] Y 1 , Y 2 and Y 3 Examples of the aromatic hydrocarbon group in the formula (I) include aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as a phenyl group, a naphthyl group, an anthryl group, a phenanthryl group, and a biphenyl group, of which a phenyl group and a naphthyl group are preferred, and a phenyl group is more preferred. Examples of the aromatic heterocyclic group in the formula (I) include aromatic heterocyclic groups having 4 to 20 carbon atoms and containing at least one heteroatom, such as a nitrogen atom, an oxygen atom, or a sulfur atom, such as a furyl group, a pyrrolyl group, a thienyl group, a pyridinyl group, a thiazolyl group, and a benzothiazolyl group, of which a furyl group, a thienyl group, a pyridinyl group, a thiazolyl group, and a benzothiazolyl group are preferred.

[0053] Y 1 , Y 2 and Y 3 may each independently be a substituted or unsubstituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring assembly. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring assembly.

[0054] Z 0 , Z 1 and Z 2 are each preferably independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms; Z 0 is more preferably a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group;1 and Z 2 is more preferably a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, or a cyano group.

[0055] Q 1 , Q 2 and Q 3 -NH-, -S-, -NR 2’ -, -O- are preferred, R 2’ is preferably a hydrogen atom, and among these, -S-, -O-, and -NH- are particularly preferable.

[0056] Among the formulae (Ar-1) to (Ar-22), the formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.

[0057] In formulas (Ar-16) to (Ar-22), Y 1 is the nitrogen atom to which it is bonded and Z 0 and may form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include those mentioned above as aromatic heterocyclic rings that Ar may have, such as a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, and a pyrrolidine ring. This aromatic heterocyclic group may have a substituent. In addition, Y 1 is the nitrogen atom to which it is bonded and Z 0 In addition, it may be the above-mentioned substituted or unsubstituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group, for example, a benzofuran ring, a benzothiazole ring, a benzoxazole ring, etc.

[0058] As the polymerizable liquid crystal compound, for example, a compound represented by the following formula (A) (hereinafter also referred to as compound (A)) is preferable. Only one type of polymerizable liquid crystal compound may be used, or two or more types may be used in combination, but when two or more types are used in combination, it is preferable that at least one type is compound (A), and it is more preferable that at least two types are compound (A).

[0059] [ka]

[0060] (In formula (A), X 1 is an oxygen atom, a sulfur atom or -NR 1 - stands for R 1 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. 1 represents a substituted or unsubstituted monovalent aromatic hydrocarbon group having 6 to 12 carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having 3 to 12 carbon atoms. 3 and Q 4 each independently represents a hydrogen atom, a substituted or unsubstituted monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms, a monovalent alicyclic hydrocarbon group having 3 to 20 carbon atoms, a substituted or unsubstituted monovalent aromatic hydrocarbon group having 6 to 20 carbon atoms, a halogen atom, a cyano group, a nitro group, -NR 2 R 3 or -SR 2 or Q 3 and Q 4 and bond to each other to form an aromatic ring or an aromatic heterocycle together with the carbon atoms to which they are attached. 2 and R 3 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. D 1 and D. 2 each independently represents a single bond, -C(=O)-O-, -C(=S)-O-, or -CR 4 R 5 -, -CR 4 R 5 -CR 6 R 7 -, -O-CR 4 R 5 -, -CR 4 R 5 -O-CR 6 R 7 -, -C(=O)-O-CR 4 R 5 -, -OC(=O)-CR 4 R 5 -, -CR 4 R 5 -OC(=O)-CR 6 R7 -, -CR 4 R 5 -C(=O)-O-CR 6 R 7 -, -NR 4 -CR 5 R 6 - or -C(=O)-NR 4 - stands for R 4 , R 5 , R 6 and R 7 each independently represents a hydrogen atom, a fluorine atom or an alkyl group having 1 to 4 carbon atoms. 1 and G 2 each independently represents a divalent alicyclic hydrocarbon group having 5 to 8 carbon atoms, a methylene group constituting the alicyclic hydrocarbon group may be replaced by an oxygen atom, a sulfur atom, or -NH-, and a methine group constituting the alicyclic hydrocarbon group may be replaced by a tertiary nitrogen atom. 1 and L 2 each independently represents a monovalent organic group; L 1 and L 2 At least one of the groups has a polymerizable group. Here, the polymerizable group is as described above.) L in compound (A) 1 is preferably a group represented by the following formula (A1), and L in compound (A) 2 is preferably a group represented by the following formula (A2).

[0061] P 1 -F 1 -(B 1 -A 1 ) k -E 1 - ... (A1) P 2 -F 2 -(B 2 -A 2 ) l -E 2 - ... (A2) (In the formula, B 1 , B 2 , E 1 and E 2 are each independently -CR 4 R5 -, -CH2-CH2-, -O-, -S-, -C(=O)-O-, -OC(=O)-O-, -CS-O-, -OC(=S)-O-, -C(=O)-NR 1 A represents -, -O-CH2-, -S-CH2- or a single bond. 1 and A 2 each independently represents a divalent alicyclic hydrocarbon group having 5 to 8 carbon atoms or a divalent aromatic hydrocarbon group having 6 to 18 carbon atoms, a methylene group constituting the alicyclic hydrocarbon group may be replaced by an oxygen atom, a sulfur atom or -NH-, and a methine group constituting the alicyclic hydrocarbon group may be replaced by a tertiary nitrogen atom. k and l each independently represent an integer of 0 to 3. F 1 and F 2 each independently represents a divalent aliphatic hydrocarbon group having 1 to 12 carbon atoms. 1 represents a hydrogen atom or a polymerizable group, and is preferably a polymerizable group. 2 represents a hydrogen atom or a polymerizable group. 1 and P 2 At least one of these may be a polymerizable group. 4 and R 5 R each independently represents a hydrogen atom, a fluorine atom, or an alkyl group having 1 to 4 carbon atoms. 1 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. Preferred examples of the compound (A) include the polymerizable liquid crystal compounds described in JP-A-2011-207765.

[0062] An example of the polymerizable liquid crystal compound different from the compound (A) is a compound containing a group represented by the following formula (X) (hereinafter, also referred to as compound (X)).

[0063] P 11 -B 11 -E 11 -B 12 -A 11 -B 13 - …(X) (In the formula, P 11 represents a polymerizable group. 11represents a divalent alicyclic hydrocarbon group or a divalent aromatic hydrocarbon group. A hydrogen atom contained in the divalent alicyclic hydrocarbon group and the divalent aromatic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a cyano group, or a nitro group, and a hydrogen atom contained in the alkyl group having 1 to 6 carbon atoms and the alkoxy group having 1 to 6 carbon atoms may be substituted with a fluorine atom. 11 -O-, -S-, -C(=O)-O-, -OC(=O)-, -OC(=O)-O-, -C(=O)-NR 16 -, -NR 16 R represents -C(=O)-, -C(=O)-, -CS- or a single bond. 16 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. 12 and B. 13 each independently represents -C≡C-, -CH=CH-, -CH2-CH2-, -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-, -OC(=O)-O-, -CH=N-, -N=CH-, -N=N-, -C(=O)-NR 16 -, -NR 16 -C(=O)-, -OCH2-, -OCF2-, -CH2O-, -CF2O-, -CH=CH-C(=O)-O-, -OC(=O)-CH=CH- or a single bond. E 11 represents an alkanediyl group having 1 to 12 carbon atoms, and a hydrogen atom contained in the alkanediyl group may be substituted with an alkoxy group having 1 to 5 carbon atoms, and a hydrogen atom contained in the alkoxy group may be substituted with a halogen atom. -CH2- constituting the alkanediyl group may be substituted with -O- or -C(=O)-. Specific examples of the polymerizable liquid crystal compound including the above-mentioned compound (A) and compound (X) include compounds having a polymerizable group among the compounds described in "3.8.6 Network (completely crosslinked type)" and "6.5.1 Liquid crystal material b. Polymerizable nematic liquid crystal material" in Liquid Crystal Handbook (edited by Liquid Crystal Handbook Editorial Committee, Maruzen Co., Ltd., published on October 30, 2000), as well as the polymerizable liquid crystal compounds described in JP-A-2010-31223, JP-A-2010-270108, JP-A-2011-6360 and JP-A-2011-207765.

[0064] The total content of the polymerizable liquid crystal compounds in 100 parts by mass of the solid content of the liquid crystal cured film of the present invention is usually 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, and more preferably 80 to 94 parts by mass. If the total content is within the above range, the orientation of the obtained liquid crystal cured film tends to be high. Here, the solid content refers to the total amount of components excluding the solvent.

[0065] [Composition for forming liquid crystal cured film] In addition to the polymerizable liquid crystal compound, the liquid crystal cured film forming composition may optionally contain other components such as a solvent, a polymerization initiator, a sensitizer, a polymerization inhibitor, and a leveling agent. Among them, it is preferable to contain a polymerization initiator in order to suitably start the polymerization reaction and form a liquid crystal cured film. It is also preferable to contain a solvent from the viewpoint of making the thickness of the obtained liquid crystal cured film uniform. The polymerizable liquid crystal molecules contained in the liquid crystal cured film forming composition are polymerized, and the liquid crystal cured film is formed.

[0066] In the liquid crystal cured film forming composition, the content of the polymerizable liquid crystal compound in 100 parts by mass of the solid content of the liquid crystal cured film forming composition is usually 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, and more preferably 80 to 94 parts by mass. If the content is within the above range, the orientation of the obtained liquid crystal cured film tends to be high. Here, the solid content refers to the total amount of components excluding the solvent from the liquid crystal cured film forming composition.

[0067] [solvent] The solvent is preferably one that can completely dissolve the polymerizable liquid crystal compound, and is preferably a solvent that is inactive to the polymerization reaction of the polymerizable liquid crystal compound.

[0068] Examples of the solvent include alcohol solvents such as methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorine-containing solvents such as chloroform and chlorobenzene; etc. Only one of these solvents may be used, or two or more of them may be used in combination.

[0069] The content of the solvent in 100 parts by mass of the composition for forming a liquid crystal cured film is preferably 50 to 98 parts by mass. Therefore, the solid content in 100 parts by mass of the composition for forming a liquid crystal cured film is preferably 2 to 50 parts by mass. When the solid content of the composition for forming a liquid crystal cured film is 50 parts by mass or less, the viscosity of the composition for forming a liquid crystal cured film is low, so that the thickness of the liquid crystal cured film becomes approximately uniform, and unevenness tends to be less likely to occur in the liquid crystal cured film. The solid content can be appropriately determined in consideration of the thickness of the liquid crystal cured film to be produced.

[0070] [Polymerization initiator] As the polymerization initiator, a photopolymerization initiator is preferable, and a photopolymerization initiator that generates radicals upon irradiation with light is more preferable.

[0071] Examples of the polymerization initiator include benzoin compounds, benzophenone compounds, benzyl ketal compounds, α-hydroxyketone compounds, α-aminoketone compounds, triazine compounds, iodonium salts, and sulfonium salts. Specific examples include Irgacure (registered trademark) 907, Irgacure 184, Irgacure 651, Irgacure 819, Irgacure 250, Irgacure 369, Irgacure 379, Irgacure 127, Irgacure 2959, Irgacure 754, Irgacure 379EG (all manufactured by BASF Japan Ltd.), Seikuol BZ, Seikuol Z, Seikuol BEE (all manufactured by Seiko Chemical Co., Ltd.), Kayacure (registered trademark), and other compounds. cure) BP100 (manufactured by Nippon Kayaku Co., Ltd.), Kayacure UVI-6992 (manufactured by Dow), ADEKA OPTOMER SP-152, ADEKA OPTOMER SP-170, ADEKA OPTOMER N-1717, ADEKA OPTOMER N-1919, ADEKA ARCLES NCI-831, ADEKA ARCLES NCI-930 (all manufactured by ADEKA Corporation), TAZ-A, TAZ-PP (all manufactured by Nippon SiberHegner AG) and TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.).

[0072] It is particularly preferable that the photopolymerization initiator has an oxime structure in its molecule.

[0073] In the present invention, a photopolymerization initiator composition is used. The photopolymerization initiator composition may contain only one type of photopolymerization initiator, or may contain two or more types of photopolymerization initiators. It is preferable that the photopolymerization initiator composition has two maximum absorption wavelengths, namely, a maximum absorption wavelength λ(A) and a maximum absorption wavelength λ(B). The maximum absorption wavelength λ(A) and the maximum absorption wavelength λ(B) satisfy the formula λ(A)<λ(B). Furthermore, the maximum absorption wavelength λ(A) and the maximum absorption wavelength λ(B) of the photopolymerization initiator and the maximum absorption wavelength λ of the polymerizable liquid crystal compound are less than or equal to λ(A). max It is more preferable that (LC) satisfies the following formula:

[0074] 20nm<λ(B) -λ max (LC) or 20nm<λ max (LC)-λ(A) Since the photopolymerization initiator has two maximum absorption wavelengths that satisfy the above formula, when the photopolymerization initiator composition and the polymerizable liquid crystal compound are irradiated with light, the light absorption of the photopolymerization initiator contained in the photopolymerization initiator composition is carried out without being inhibited by the light absorption of the polymerizable liquid crystal compound, and a sufficient amount of radicals is generated to initiate the polymerization reaction, so that the polymerization reaction can be carried out suitably.

[0075] Here, when the liquid crystal cured film-forming composition contains two or more polymerizable liquid crystal compounds, the λ max It is preferable that (LC) satisfies the above formula. More preferably, λ of all the polymerizable liquid crystal compounds contained therein satisfies the above formula. max (LC) satisfies the above formula.

[0076] In addition to the photopolymerization initiator composition described above, other photopolymerization initiators may be used as the photopolymerization initiator. The other photopolymerization initiators are those having a maximum absorption wavelength that is different from the maximum absorption wavelength λ of the photopolymerization initiator and the maximum absorption wavelength λ of the polymerizable liquid crystal compound. max (LC) does not satisfy the above formula.

[0077] The photopolymerization initiator contained in the photopolymerization initiator composition is preferably used with two or more types of photopolymerization initiators with different main photosensitive wavelengths in order to efficiently use ultraviolet light with a wavelength of less than 350 nm and ultraviolet light with a wavelength of 350 nm or more. As the photopolymerization initiator that can efficiently absorb ultraviolet light with a wavelength of less than 350 nm, it is preferable to use an α-acetophenone compound, and examples of the α-acetophenone compound include 2-methyl-2-morpholino-1-(4-methylsulfanylphenyl)propan-1-one, 2-dimethylamino-1-(4-morpholinophenyl)-2-benzylbutan-1-one, and 2-dimethylamino-1-(4-morpholinophenyl)-2-(4-methylphenylmethyl)butan-1-one, and more preferably 2-methyl-2-morpholino-1-(4-methylsulfanylphenyl)propan-1-one and 2-dimethylamino-1-(4-morpholinophenyl)-2-benzylbutan-1-one. Commercially available α-acetophenone compounds include Irgacure 369, Irgacure 379EG, Irgacure 907 (all manufactured by BASF Japan Ltd.) and Seikuol BEE (manufactured by Seiko Chemical Co., Ltd.).

[0078] In addition, from the viewpoint of more efficiently proceeding with the polymerization reaction in the depth of the liquid crystal cured film, it is preferable to use a photopolymerization initiator that can efficiently utilize ultraviolet light having a wavelength of 350 nm or more. For example, a photopolymerization initiator having an absorbance of 0.10 or more, more preferably 0.10 or more and 0.20 or less at 350 nm in a 0.001% by mass chloroform solution can be used. As a photopolymerization initiator that can efficiently absorb ultraviolet light having a wavelength of 350 nm or more, a triazine compound or an oxime ester type carbazole compound is preferable, and from the viewpoint of sensitivity, an oxime ester type carbazole compound is more preferable. Examples of the oxime ester type carbazole compound include 1,2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime), and the like. Commercially available oxime ester carbazole compounds include Irgacure OXE-01, Irgacure OXE-02, Irgacure OXE-03 (all manufactured by BASF Japan Ltd.), ADEKA Optomer N-1919, ADEKA Arcles NCI-831 (all manufactured by ADEKA Corporation), and the like.

[0079] When two or more different photopolymerization initiators are used, it is more preferable that at least one of the photopolymerization initiators has an oxime structure in its molecule.

[0080] In addition, from the viewpoint of more efficiently proceeding with the polymerization reaction, the photopolymerization initiator composition or the photopolymerization initiator preferably has two or more maximum absorptions at wavelengths of 300 nm or more. Examples of photopolymerization initiators having two or more maximum absorptions at wavelengths of 300 nm or more include ADEKA ARCLES NCI-831 (manufactured by ADEKA CORPORATION) and IRGACURE OXE-03 (manufactured by BASF Japan Ltd.).

[0081] When two or more different photopolymerization initiators are used as the photopolymerization initiator, it is more preferable that at least one of the photopolymerization initiators has an oxime structure in its molecule.

[0082] The amount of the photopolymerization initiator composition satisfying the above formula is usually 1 to 20 parts by mass, preferably 3 to 18 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound. If the amount of the photopolymerization initiator composition is within the above range, it is preferable because the alignment of the polymerizable liquid crystal compound is not easily disturbed. In addition, the amount of the photopolymerization initiator contained in the photopolymerization initiator composition, which has at least one maximum absorption wavelength λ1 that satisfies the following formula (II), is preferably 1 to 20 parts by mass, more preferably 3 to 18 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound.

[0083] 20nm<|λ1-λ max (LC) | (II) When the photopolymerization initiator composition contains two or more kinds of photopolymerization initiators, the photopolymerization initiator composition contains a photopolymerization initiator having a main photosensitive wavelength closer to the wavelength of the ultraviolet light to be irradiated thereto in an amount of preferably 5% by mass or more, more preferably 10% by mass or more, based on 100% by mass of the photopolymerization initiator composition, which allows efficient polymerization of the polymerizable liquid crystal compound.

[0084] [Sensitizer] By including a sensitizer in the liquid crystal cured film-forming composition, the polymerization reaction of the polymerizable liquid crystal compound in the composition can be further promoted.

[0085] The sensitizer is preferably a photosensitizer. Examples of the sensitizer include xanthone compounds such as xanthone and thioxanthone (2,4-diethylthioxanthone, 2-isopropylthioxanthone, etc.), anthracene compounds such as anthracene and alkoxy group-containing anthracene (dibutoxyanthracene, etc.), phenothiazine, rubrene, etc.

[0086] The content of the sensitizer is preferably from 0.1 to 30 parts by mass, more preferably from 0.5 to 10 parts by mass, and further preferably from 0.5 to 8 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound.

[0087] [Polymerization inhibitor] By using a polymerization inhibitor, the degree of progress of the polymerization reaction of the polymerizable liquid crystal compound can be controlled.

[0088] Examples of the polymerization inhibitor include radical scavengers such as phenolic compounds such as 2,6-di-tert-butyl-4-methylphenol, sulfur-based compounds such as dilaurylthiodipropionate, phosphorus-based compounds such as trioctyl phosphite, and amine compounds containing a hindered amine structure, typified by 2,2,6,6-tetramethylpiperidine.

[0089] As the polymerization inhibitor, a phenol-based compound is preferred because it causes less coloring of the cured liquid crystal film.

[0090] The content of the polymerization inhibitor is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. If the content of the polymerization inhibitor is within the above range, it is preferable because the polymerizable liquid crystal compound can be polymerized without disturbing the alignment. Only one type of polymerization inhibitor may be used, or two or more types may be used in combination.

[0091] [Leveling agent] The leveling agent is an additive that adjusts the fluidity of the composition and makes the film obtained by applying the composition flatter, and examples of such additives include surfactants. Preferred leveling agents include leveling agents mainly composed of polyacrylate compounds such as "BYK-361N" (manufactured by BYK Chemie) and leveling agents mainly composed of fluorine atom-containing compounds such as Surflon (registered trademark) "S-381" (manufactured by AGC Seimi Chemical Co., Ltd.).

[0092] The content of the leveling agent is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound. When the content of the leveling agent is within the above range, the polymerizable liquid crystal compound is easily aligned horizontally, and the obtained liquid crystal cured film tends to be smoother, which is preferable. The liquid crystal cured film forming composition may contain two or more types of leveling agents.

[0093] [Physical properties of liquid crystal cured film] The liquid crystal cured film of the present invention is usually a film having a thickness of 5 μm or less, in which the polymerizable liquid crystal compound is cured in an aligned state, and preferably a film in which the polymerizable liquid crystal compound is cured in a state in which the polymerizable liquid crystal compound is aligned horizontally or vertically to the substrate surface.

[0094] The thickness of the liquid crystal cured film is preferably 0.5 to 5 μm, more preferably 1 to 3 μm. The thickness of the liquid crystal cured film can be measured by an interference thickness meter, a laser microscope, or a stylus type thickness meter.

[0095] In a liquid crystal cured film in which a polymerizable liquid crystal compound is cured while being aligned in a horizontal direction relative to a substrate surface, the birefringence Δn(λ) for light with a wavelength of λ nm preferably satisfies the optical properties represented by the following formulas (1) and (2), and more preferably satisfies the optical properties represented by the following formulas (1), (2), and (3).

[0096] Re(450) / Re(550)≦1.00 …(1) 1.00≦Re(650) / Re(550) …(2) (In the formula, Re(450) represents an in-plane retardation value for light with a wavelength of 450 nm, Re(550) represents an in-plane retardation value for light with a wavelength of 550 nm, and Re(650) represents an in-plane retardation value for light with a wavelength of 650 nm.) 100nm <Re(550)<160nm …(3) (In the formula, Re(550) represents an in-plane retardation value for light having a wavelength of 550 nm.) The liquid crystal cured film of the present invention has a maximum absorption wavelength in the range of 300 nm or more and 380 nm or less, and therefore can protect the elements of a liquid crystal display device or an EL display device from ultraviolet rays that may cause deterioration of the elements. The liquid crystal cured film of the present invention preferably has absorption in the wavelength range of 330 nm or more and 380 nm or less. That is, the liquid crystal cured film is preferably formed from a polymerizable liquid crystal compound having a maximum absorption wavelength in the wavelength range of 300 nm or more and 380 nm or less, and more preferably formed from a polymerizable liquid crystal compound having a maximum absorption wavelength in the wavelength range of 330 nm or more and 380 nm or less.

[0097] A liquid crystal cured film in which the polymerizable liquid crystal compound is cured in a state where it is aligned in the vertical direction to the substrate surface preferably satisfies the following formula (4).

[0098] nz>nx≒ny …(4) (In the formula, nz represents the refractive index in the thickness direction, nx represents the refractive index in the direction in which the maximum refractive index occurs in the plane, and ny represents the refractive index in the direction perpendicular to the nx direction in the plane.) The in-plane retardation value of the liquid crystal cured film can be adjusted by the thickness of the liquid crystal cured film. Since the in-plane retardation value is determined by the following formula (5), the desired in-plane retardation value (Re(λ)) can be obtained by adjusting Δn(λ) and the film thickness d.

[0099] Re(λ)=d×Δn(λ) …(5) (In the formula, Re(λ) represents an in-plane retardation value at a wavelength of λ nm, d represents a film thickness, and Δn(λ) represents a birefringence at a wavelength of λ nm.) The birefringence Δn(λ) is obtained by measuring the in-plane retardation value and dividing it by the thickness of the liquid crystal cured film. A specific measurement method is shown in the examples, but at this time, by measuring a film formed on a substrate such as a glass substrate that does not have an in-plane retardation in the substrate itself, the properties of the liquid crystal cured film can be measured.

[0100] In the liquid crystal cured film in which the polymerizable liquid crystal compound is cured in a state where it is aligned in the vertical direction to the substrate surface, Re(550) is preferably 0 to 10 nm, more preferably 0 to 5 nm. The retardation value Rth in the thickness direction is preferably -10 to -300 nm, more preferably -20 to -200 nm. The liquid crystal cured film that satisfies the formula (4) and has Re(550) and Rth within the above ranges is particularly suitable for compensation of an IPS (in-plane switching) mode liquid crystal display device.

[0101] Rth is a retardation value R measured by tilting the liquid crystal cured film plane by 40 degrees with respect to the in-plane fast axis as the tilt axis. 40 and the in-plane retardation value R0. That is, Rth can be calculated from the in-plane retardation value R0, the retardation value R measured by inclining the liquid crystal cured film plane by 40 degrees with respect to the fast axis as the tilt axis. 40 From the thickness d of the cured liquid crystal film, and the average refractive index n0 of the cured liquid crystal film, nx, ny, and nz are calculated by the following formulas (9) to (11), and these values ​​are substituted into formula (8) to perform calculation.

[0102] Rth = [(nx + ny) / 2 - nz] × d … (8) R0 = (nx - ny) × d … (9) R 40 =(nx-ny')×d / cos(φ) …(10) (nx+ny+nz) / 3=n0…(11) Where: φ=sin -1 [sin(40°) / n0] ny'=ny×nz / 〔ny 2 ×sin 2 (φ)+nz 2 ×cos 2 (φ) 1 / 2 It is.

[0103] [Base material] Examples of the substrate include glass substrates and plastic substrates, and preferably plastic substrates. Examples of the plastics constituting the plastic substrate include polyolefins such as polyethylene, polypropylene, and norbornene-based polymers; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylic acid esters; polyacrylic acid esters; cellulose esters such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; polyphenylene sulfide, and polyphenylene oxide. Examples of commercially available cellulose ester substrates include "Fujitac Film" (manufactured by Fuji Photo Film Co., Ltd.); "KC8UX2M", "KC8UY", and "KC4UY" (all manufactured by Konica Minolta Opto Co., Ltd.).

[0104] Examples of commercially available cyclic olefin resins include "Topas" (registered trademark) (manufactured by Ticona, Germany), "Arton" (registered trademark) (manufactured by JSR Corporation), "ZEONOR" (registered trademark), "ZEONEX" (registered trademark) (all manufactured by Zeon Corporation), and "Apel" (registered trademark) (manufactured by Mitsui Chemicals, Inc.). Such cyclic olefin resins can be formed into a film by known means such as a solvent casting method or a melt extrusion method to form a substrate. Commercially available cyclic olefin resin substrates can also be used. Examples of commercially available cyclic olefin resin substrates include "S-Cina" (registered trademark), "SCA40" (registered trademark) (all manufactured by Sekisui Chemical Co., Ltd.), "ZEONOR Film" (registered trademark) (manufactured by Optes Co., Ltd.), and "Arton Film" (registered trademark) (manufactured by JSR Corporation).

[0105] The thickness of the substrate is preferably thin in terms of the mass that can be practically handled, but if it is too thin, the strength decreases and the processability tends to be poor. The thickness of the substrate is usually 5 to 300 μm, and preferably 20 to 200 μm.

[0106] [Alignment film] The alignment film is a film having an alignment regulating force for aligning a polymerizable liquid crystal compound in a desired direction. Examples of the alignment film include an alignment film made of an orientable polymer, a photoalignment film, and a groove alignment film.

[0107] The alignment film facilitates the alignment of the polymerizable liquid crystal compound. The state of liquid crystal alignment, such as horizontal alignment, vertical alignment, hybrid alignment, and tilt alignment, varies depending on the properties of the alignment film and the polymerizable liquid crystal compound, and the combination can be selected arbitrarily. If the alignment film is a material that exerts horizontal alignment as an alignment control force, the polymerizable liquid crystal compound can form a horizontal alignment or a hybrid alignment, and if the alignment film is a material that exerts vertical alignment, the polymerizable liquid crystal compound can form a vertical alignment or a tilt alignment. The expressions "horizontal" and "vertical" represent the direction of the long axis of the aligned polymerizable liquid crystal compound when the liquid crystal cured film plane is used as a reference. Horizontal alignment is an alignment in which the long axis of the aligned polymerizable liquid crystal compound is parallel to the optically anisotropic layer plane. "Parallel" here means an angle of 0°±20° with respect to the optically anisotropic layer plane. Vertical alignment is an alignment in which the long axis of the aligned polymerizable liquid crystal compound is perpendicular to the liquid crystal cured film plane. "Vertical" here means an angle of 90°±20° with respect to the liquid crystal cured film plane.

[0108] When the alignment film is made of an alignment polymer, the alignment regulating force can be arbitrarily adjusted by the surface state of the polymer or the rubbing conditions, and when the alignment film is made of a photoalignment polymer, the alignment regulating force can be arbitrarily adjusted by the polarized light irradiation conditions for the polymer, etc. The liquid crystal alignment of the polymerizable liquid crystal compound can also be controlled by selecting the physical properties such as the surface tension and liquid crystallinity of the polymerizable liquid crystal compound.

[0109] When the liquid crystal cured film satisfies formula (4), the liquid crystal alignment of the polymerizable liquid crystal compound forming the liquid crystal cured film is preferably vertical alignment. In order to vertically align the polymerizable liquid crystal compound, it is preferable to use an alignment film having a non-polar substituent group consisting of silicon atoms, fluorine atoms, etc., and as the alignment film, a material generally used as a liquid crystal alignment film for a vertical alignment type liquid crystal display element, such as those described in Japanese Patent No. 4605016, Japanese Patent No. 4985906, Japanese Patent No. 4502119, and WO2008 / 117760, can be used.

[0110] The alignment film formed between the substrate and the liquid crystal cured film is preferably a film that is insoluble in a solvent used when forming the liquid crystal cured film on the alignment film and has heat resistance in a heat treatment for removing the solvent and orienting the liquid crystal. Examples of the alignment film include an alignment film made of an orienting polymer, a photoalignment film, and a groove alignment film.

[0111] The thickness of the alignment film is usually 10 to 500 nm, and preferably 10 to 200 nm.

[0112] [Alignment film made of oriented polymer] An alignment film made of an alignment polymer is usually obtained by applying a composition in which an alignment polymer is dissolved in a solvent (hereinafter also referred to as an alignment polymer composition) to a substrate and removing the solvent, or by applying an alignment polymer composition to a substrate, removing the solvent, and rubbing the substrate (rubbing method).

[0113] The concentration of the orienting polymer in the orienting polymer composition may be within a range in which the orienting polymer material can be completely dissolved in the solvent, and is preferably 0.1 to 20 mass % in terms of solid content relative to the solution, and more preferably 0.1 to 10 mass %.

[0114] Examples of commercially available oriented polymer compositions include SUNEVER (registered trademark) (manufactured by Nissan Chemical Industries, Ltd.) and OPTOMER (registered trademark) (manufactured by JSR Corporation).

[0115] [Photo-alignment film] A photo-alignment film is usually obtained by applying a composition containing a polymer or monomer having a photoreactive group and a solvent (hereinafter also referred to as a composition for forming a photo-alignment film) to a substrate and irradiating the substrate with polarized light (preferably polarized UV). A photo-alignment film is more preferable in that the direction of the alignment control force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.

[0116] The photoreactive group refers to a group that generates liquid crystal alignment ability by irradiation with light. Specifically, the photoreactive group is a group that generates a photoreaction that is the origin of liquid crystal alignment ability, such as molecular alignment induction or isomerization reaction, dimerization reaction, photocrosslinking reaction, or photodecomposition reaction, which occurs by irradiation with light. Among the photoreactive groups, a group that causes a dimerization reaction or a photocrosslinking reaction is preferred in terms of excellent alignment ability. As the photoreactive group that can generate the above reaction, a group having an unsaturated bond, particularly a double bond, is preferred, and a group having at least one selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond), and a carbon-oxygen double bond (C=O bond) is particularly preferred.

[0117] The content of the polymer or monomer having a photoreactive group in the composition for forming a photo-alignment film is preferably 0.2% by mass or more, particularly preferably 0.3 to 10% by mass. The composition for forming a photo-alignment film may contain a polymer material such as polyvinyl alcohol or polyimide, or a photosensitizer, within a range that does not significantly impair the properties of the photo-alignment film.

[0118] The polarized light may be irradiated directly onto the composition obtained by removing the solvent from the composition for forming a photo-alignment film coated on the substrate, or may be irradiated from the substrate side with polarized light and then transmitted to irradiate the composition. It is particularly preferable that the polarized light is substantially parallel light. The wavelength of the polarized light to be irradiated is preferably in a wavelength range in which the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) having a wavelength of 250 to 400 nm is particularly preferable.

[0119] If masking is performed when rubbing or polarized light irradiation is performed, a plurality of regions (patterns) in which the liquid crystal alignment directions are different can be formed.

[0120] [Grove alignment film] A groove alignment film is a film that has a concave-convex pattern or multiple grooves on the film surface. When a polymerizable liquid crystal compound is applied to a film that has multiple linear grooves arranged at equal intervals, the liquid crystal molecules are aligned in the direction along the grooves.

[0121] Methods for obtaining a groove alignment film include a method of forming a concave-convex pattern by exposing a photosensitive polyimide film surface through an exposure mask having slits in a pattern shape, developing and rinsing the film, forming a layer of UV-curable resin before curing on a plate-shaped master having grooves on the surface, transferring the resin layer to a substrate and curing the resin, and pressing a roll-shaped master having a plurality of grooves against a film of UV-curable resin before curing formed on a substrate to form concave-convex patterns, followed by curing the film, etc. Specific examples of the method include the methods described in JP-A-6-34976 and JP-A-2011-242743.

[0122] [Embodiment 2: Optical film] The present invention may be an optical film including the liquid crystal cured film according to the first embodiment of the present invention.

[0123] [Embodiment 3: Circularly polarizing plate] The present invention may be a circular polarizing plate including the liquid crystal cured film according to the first embodiment of the present invention or the optical film according to the second embodiment of the present invention, and a polarizing plate.

[0124] The circularly polarizing plate can be produced, for example, by the following methods (i) and (ii).

[0125] (i) A liquid crystal cured film is formed on a substrate or on an alignment film on the substrate, and the liquid crystal cured film is bonded to a transfer recipient (here, a polarizer or a polarizing plate) via a first adhesive layer. The substrate or the alignment film together with the substrate is removed to form a laminate including the liquid crystal cured film, the adhesive layer and the transfer recipient.

[0126] (ii) When only the substrate is removed in the above (i), a circular polarizing plate can be manufactured by forming a second adhesive layer on the alignment film of the obtained laminate, in which a polarizer or polarizing plate, a first adhesive layer, a liquid crystal cured film, an alignment film, and a second adhesive layer are laminated in this order. When the alignment film is removed together with the substrate in the above (i), a circular polarizing plate can be manufactured by forming a second adhesive layer on the liquid crystal cured film of the obtained laminate, in which a polarizer or polarizing plate, a first adhesive layer, a liquid crystal cured film, and a second adhesive layer are laminated in this order.

[0127] The liquid crystal cured film may be a film obtained by curing the polymerizable liquid crystal compound in a state where the polymerizable liquid crystal compound is aligned in a direction perpendicular to or parallel to the surface of the substrate.

[0128] [Method of manufacturing laminate] The laminate can be manufactured by the method (i) in the manufacturing method of the circularly polarizing plate. The adhesive layer may be formed on the liquid crystal cured film or on the transfer body. When an alignment film is present between the substrate and the liquid crystal cured film, the alignment film may be removed together with the substrate.

[0129] A substrate having a functional group on its surface that forms a chemical bond with a liquid crystal cured film or an alignment film, etc., tends to be difficult to remove because the functional group forms a chemical bond with the liquid crystal cured film or the alignment film, etc. Therefore, when removing the substrate by peeling, a substrate having a small number of functional groups on its surface is preferred, and a substrate that has not been subjected to a surface treatment that forms a functional group on its surface is preferred.

[0130] Since an alignment film having a functional group that forms a chemical bond with a substrate tends to have a strong adhesive force between the substrate and the alignment film, when the substrate is peeled off and removed, an alignment film having a small number of functional groups that form a chemical bond with the substrate is preferred. The solution of the alignment polymer composition and the photoalignment film forming composition preferably does not contain a reagent that crosslinks the substrate and the alignment film, and further preferably does not contain a component such as a solvent that dissolves the substrate.

[0131] An alignment film having a functional group that forms a chemical bond with the liquid crystal cured film tends to have a strong adhesive force between the liquid crystal cured film and the alignment film. Therefore, when removing the alignment film together with the substrate, an alignment film having a small number of functional groups that form a chemical bond with the liquid crystal cured film is preferred. The solution of the alignment polymer composition and the photo-alignment film forming composition, etc., preferably does not contain a reagent that crosslinks the liquid crystal cured film and the alignment film.

[0132] A liquid crystal cured film having a functional group that forms a chemical bond with an alignment film tends to have a strong adhesive force between the alignment film and the liquid crystal cured film. Therefore, when removing the substrate or removing the alignment film together with the substrate, a liquid crystal cured film having a small number of functional groups that form a chemical bond with the substrate or alignment film is preferred. The liquid crystal cured film forming composition preferably does not contain a reagent that crosslinks the substrate or alignment film with the liquid crystal cured film.

[0133] [First adhesive layer] The first adhesive layer is formed from an adhesive. Examples of the adhesive include a pressure-sensitive adhesive, a drying-hardening type adhesive, and a chemical reaction type adhesive. Examples of the chemical reaction type adhesive include an energy ray curing type adhesive. A preferred adhesive layer is a pressure-sensitive adhesive or an active energy ray curing type adhesive.

[0134] [Adhesive] The adhesive typically contains a polymer and may contain a solvent.

[0135] Examples of the polymer include an acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyether, etc. Among them, an acrylic pressure-sensitive adhesive containing an acrylic polymer is preferable because it has excellent optical transparency, appropriate wettability and cohesive strength, excellent adhesion, and further has high weather resistance and heat resistance, and is unlikely to lift or peel off under heating or humidifying conditions.

[0136] As the acrylic polymer, a copolymer of a (meth)acrylate in which the alkyl group of the ester moiety is an alkyl group having 1 to 20 carbon atoms, such as a methyl group, an ethyl group, or a butyl group (hereinafter, acrylate and methacrylate may be collectively referred to as (meth)acrylate, and acrylic acid and methacrylic acid may be collectively referred to as (meth)acrylic acid) and a (meth)acrylic monomer having a functional group, such as (meth)acrylic acid or hydroxyethyl (meth)acrylate, is preferred.

[0137] A pressure-sensitive adhesive containing such a copolymer is preferable because it has excellent adhesion and can be removed relatively easily without leaving any adhesive residue on the display device when the pressure-sensitive adhesive layer is attached to the display device and then removed. The glass transition temperature of the acrylic polymer is preferably 25° C. or lower, more preferably 0° C. or lower. The mass average molecular weight of such an acrylic polymer is preferably 100,000 or higher.

[0138] Examples of the solvent include water; alcohol solvents such as methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, methyl amyl ketone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorine-substituted hydrocarbon solvents such as chloroform and chlorobenzene; etc. These solvents may be used alone or in combination of two or more.

[0139] The adhesive may contain a light diffusing agent. The light diffusing agent is an additive that imparts light diffusibility to the adhesive, and may be fine particles having a refractive index different from that of the polymer contained in the adhesive. Examples of light diffusing agents include fine particles made of inorganic compounds and fine particles made of organic compounds (polymers). Many of the polymers contained as active ingredients in adhesives, including acrylic polymers, have a refractive index of about 1.4, so it is preferable to appropriately select a light diffusing agent from those having a refractive index of 1 to 2. The refractive index difference between the polymer contained as an active ingredient in the adhesive and the light diffusing agent is usually 0.01 or more, and from the viewpoint of the brightness and displayability of the display device, it is preferably 0.01 to 0.5. The fine particles used as the light diffusing agent are preferably spherical fine particles, more preferably near monodisperse fine particles, and more preferably fine particles having an average particle size of 2 to 6 μm.

[0140] The refractive index is measured by the common minimum deviation method or by an Abbe refractometer.

[0141] Examples of fine particles made of an inorganic compound include aluminum oxide (refractive index: 1.76) and silicon oxide (refractive index: 1.45).

[0142] Examples of fine particles made of organic compounds (polymers) include melamine beads (refractive index 1.57), polymethyl methacrylate beads (refractive index 1.49), methyl methacrylate / styrene copolymer resin beads (refractive index 1.50 to 1.59), polycarbonate beads (refractive index 1.55), polyethylene beads (refractive index 1.53), polystyrene beads (refractive index 1.6), polyvinyl chloride beads (refractive index 1.46), and silicone resin beads (refractive index 1.46).

[0143] The content of the light diffusing agent is usually 3 to 30 parts by mass with respect to 100 parts by mass of the polymer.

[0144] The haze value of the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive having the light diffusing agent dispersed therein is preferably 20 to 80% from the viewpoints of ensuring the brightness of the display device and preventing bleeding or blurring of the displayed image. The haze value is a value expressed by "(diffuse transmittance / total light transmittance)×100(%)" and is measured in accordance with JIS K 7105.

[0145] The thickness of the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive is not particularly limited since it is determined according to the adhesive strength, etc., but is usually 1 to 40 μm. From the viewpoints of processability, durability, etc., the thickness is preferably 3 to 25 μm, more preferably 5 to 20 μm. By setting the thickness of the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive to 5 to 20 μm, it is possible to maintain brightness when the display device is viewed from the front or obliquely, and to make it difficult for bleeding or blurring of the displayed image to occur.

[0146] [Dry-curing adhesive] The dry-setting adhesive may contain a solvent.

[0147] Examples of the dry-solidifying adhesive include a composition containing, as a main component, a polymer of a monomer having a protonic functional group such as a hydroxyl group, a carboxyl group, or an amino group and an ethylenically unsaturated group, or a urethane resin, and further containing a crosslinking agent or a curing compound such as a polyaldehyde, an epoxy compound, an epoxy resin, a melamine compound, a zirconia compound, or a zinc compound.

[0148] Examples of polymers of monomers having a protic functional group such as a hydroxyl group, a carboxyl group, or an amino group, and an ethylenically unsaturated group include ethylene-maleic acid copolymers, itaconic acid copolymers, acrylic acid copolymers, acrylamide copolymers, saponified polyvinyl acetate, and polyvinyl alcohol resins.

[0149] Examples of the polyvinyl alcohol resin include polyvinyl alcohol, partially saponified polyvinyl alcohol, fully saponified polyvinyl alcohol, carboxyl group-modified polyvinyl alcohol, acetoacetyl group-modified polyvinyl alcohol, methylol group-modified polyvinyl alcohol, and amino group-modified polyvinyl alcohol, etc. The content of the polyvinyl alcohol resin in the aqueous pressure-sensitive adhesive is usually 1 to 10 parts by mass, and preferably 1 to 5 parts by mass, based on 100 parts by mass of water.

[0150] Examples of the urethane resin include polyester ionomer urethane resin. The polyester ionomer urethane resin referred to here is a urethane resin having a polyester skeleton, into which a small amount of an ionic component (hydrophilic component) is introduced. The ionomer urethane resin is emulsified in water to form an emulsion without using an emulsifier, and can be used as a water-based adhesive. When using a polyester ionomer urethane resin, it is effective to add a water-soluble epoxy compound as a crosslinking agent.

[0151] Examples of epoxy resins include polyamide epoxy resins obtained by reacting epichlorohydrin with polyamide polyamines obtained by reacting polyalkylene polyamines such as diethylenetriamine or triethylenetetramine with dicarboxylic acids such as adipic acid. Commercially available products of such polyamide epoxy resins include "Sumirez Resin (registered trademark) 650" and "Sumirez Resin 675" (both manufactured by Sumika Chemtex Corporation), and "WS-525" (manufactured by Nippon PMC Corporation). When an epoxy resin is blended, the amount of the epoxy resin added is usually 1 to 100 parts by mass, preferably 1 to 50 parts by mass, based on 100 parts by mass of the polyvinyl alcohol resin.

[0152] The thickness of the adhesive layer formed from the dry-solidifying adhesive is usually 0.001 to 5 μm, preferably 0.01 to 2 μm, and more preferably 1 μm or less. If the adhesive layer formed from the dry-solidifying adhesive is too thick, the liquid crystal cured film is likely to have a poor appearance.

[0153] [Active energy ray curing adhesive] The active energy ray curable adhesive may contain a solvent. The active energy ray curable adhesive is an adhesive that cures when irradiated with active energy rays.

[0154] Examples of active energy ray curable adhesives include cationically polymerizable adhesives containing an epoxy compound and a cationic polymerization initiator, radically polymerizable adhesives containing an acrylic curing component and a radical polymerization initiator, adhesives containing both a cationic polymerizable curing component such as an epoxy compound and a radically polymerizable curing component such as an acrylic compound, and further containing a cationic polymerization initiator and a radical polymerization initiator, and adhesives that do not contain these polymerization initiators and are cured by irradiating an electron beam. Preferably, the adhesive is a radically polymerizable active energy ray curable adhesive containing an acrylic curing component and a radical polymerization initiator. Also, a cationically polymerizable active energy ray curable adhesive containing an epoxy compound and a cationic polymerization initiator that can be used substantially without a solvent is preferred.

[0155] Examples of epoxy compounds include glycidyl ethers of aromatic compounds or chain compounds having a hydroxyl group, glycidyl aminations of compounds having an amino group, epoxidized compounds of chain compounds having a C-C double bond (C=C), and alicyclic epoxy compounds in which a glycidyloxy group or an epoxyethyl group is bonded directly or via an alkylene to a saturated carbon ring, or an epoxy group is bonded directly to a saturated carbon ring. These epoxy compounds may be used alone or in combination of two or more. Among them, alicyclic epoxy compounds are preferred because they have excellent cationic polymerizability.

[0156] Commercially available epoxy compounds include the jER series (manufactured by Mitsubishi Chemical Corporation), Epicron (manufactured by DIC Corporation), Epotohto (registered trademark) (manufactured by Tohto Kasei Co., Ltd.), Adeka Resin (registered trademark) (manufactured by ADEKA Corporation), Denacol (registered trademark) (manufactured by Nagase ChemteX Corporation), Dow Epoxy (manufactured by Dow Chemical Co., Ltd.), and Tepic (registered trademark) (manufactured by Nissan Chemical Industries, Ltd.). Alicyclic epoxy compounds include the Celloxide series and Cyclomer (all manufactured by Daicel Corporation), and Cyracure UVR series (manufactured by Dow Chemical Co., Ltd.).

[0157] The active energy ray curable adhesive containing an epoxy compound may further contain a compound other than the epoxy compound. Examples of the compound other than the epoxy compound include an oxetane compound and an acrylic compound. Among them, it is preferable to use an oxetane compound in combination because it may be possible to accelerate the curing speed in cationic polymerization.

[0158] Examples of the oxetane compound include the "ARON OXETANE" (registered trademark) series (manufactured by Toagosei Co., Ltd.) and the "ETERNACOLL" (registered trademark) series (manufactured by Ube Industries, Ltd.).

[0159] The active energy ray-curable adhesive containing an epoxy compound or an oxetane compound is preferably used without a solvent.

[0160] The cationic polymerization initiator is a compound that generates cationic species upon irradiation with active energy rays such as ultraviolet rays, and examples of such initiators include aromatic diazonium salts, onium salts such as aromatic iodonium salts and aromatic sulfonium salts, and iron-arene complexes. These cationic polymerization initiators may be used alone or in combination of two or more.

[0161] Commercially available cationic polymerization initiators include the "Kayarad" (registered trademark) series (manufactured by Nippon Kayaku Co., Ltd.), the "Cyracure UVI" series (manufactured by The Dow Chemical Company), the "CPI" series (manufactured by San-Apro Ltd.), "TAZ", "BBI" and "DTS" (all manufactured by Midori Chemical Co., Ltd.), the "ADEKA Optomer" series (manufactured by ADEKA Corporation), and "RHODORSIL" (registered trademark) (manufactured by Rhodia Corporation).

[0162] The content of the cationic polymerization initiator is usually 0.5 to 20 parts by mass, and preferably 1 to 15 parts by mass, based on 100 parts by mass of the active energy ray-curable adhesive.

[0163] Examples of the acrylic curing component include (meth)acrylates such as methyl (meth)acrylate and hydroxyethyl (meth)acrylate, and (meth)acrylic acid.

[0164] Examples of the radical polymerization initiator include a hydrogen abstraction type photoradical generator and a cleavage type photoradical generator.

[0165] Examples of the hydrogen abstraction type photoradical generator include naphthalene derivatives such as 1-methylnaphthalene, anthracene derivatives, pyrene derivatives, carbazole derivatives, benzophenone derivatives, thioxanthone derivatives, and coumarin derivatives.

[0166] Examples of the cleavage type photoradical generator include aryl alkyl ketones such as benzoin ether derivatives and acetophenone derivatives, oxime ketones, acylphosphine oxides, S-phenyl thiobenzoates, titanocenes, and polymerized derivatives thereof.

[0167] Among the cleavage-type photoradical generators, acylphosphine oxides are preferred, and specifically, trimethylbenzoyldiphenylphosphine oxide (trade name "DAROCURE TPO"; manufactured by BASF Japan Ltd.), bis(2,6-dimethoxy-benzoyl)-(2,4,4-trimethyl-pentyl)-phosphine oxide (trade name "CGI 403"; manufactured by BASF Japan Ltd.), or bis(2,4,6-trimethylbenzoyl)-2,4-dipentoxyphenylphosphine oxide (trade name "Irgacure819"; manufactured by BASF Japan Ltd.) are preferred.

[0168] The active energy ray-curable adhesive may contain a sensitizer. The content of the sensitizer is preferably 0.1 to 20 parts by mass relative to 100 parts by mass of the active energy ray-curable adhesive.

[0169] The active energy ray-curable adhesive may further contain an ion trapping agent, an antioxidant, a chain transfer agent, a tackifier, a thermoplastic resin, a filler, a flow control agent, a plasticizer, an antifoaming agent, and the like.

[0170] In this specification, the active energy ray is defined as an energy ray capable of decomposing a compound that generates an active species to generate an active species. Examples of such an active energy ray include visible light, ultraviolet light, infrared light, X-rays, α-rays, β-rays, γ-rays, and electron beams, and ultraviolet light and electron beams are preferred.

[0171] The accelerating voltage of the electron beam irradiation is usually 5 to 300 kV, preferably 10 to 250 kV. The irradiation dose is usually 5 to 100 kGy, preferably 10 to 75 kGy. The electron beam irradiation is usually performed in an inert gas, but may be performed in the air or with a small amount of oxygen introduced.

[0172] The UV irradiation intensity is usually 10 to 5,000 mW / cm 2The ultraviolet irradiation intensity is preferably an intensity in a wavelength region effective for activating a cationic polymerization initiator or a radical polymerization initiator. When irradiating once or multiple times with such an ultraviolet irradiation intensity, the cumulative light amount is 10 to 3,000 mJ / cm 2 , preferably 50 to 2,000 mJ / cm 2 , more preferably 100 to 1,000 mJ / cm 2 When the accumulated light amount is less than this range, the polymerizable liquid crystal compound may not be cured sufficiently, and good transferability may not be obtained. On the other hand, when the accumulated light amount is more than this range, the optical film including the liquid crystal cured film may be colored.

[0173] Examples of ultraviolet light sources include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, carbon arc lamps, tungsten lamps, gallium lamps, excimer lasers, LED light sources emitting light with a wavelength of 380 to 440 nm, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps.

[0174] Examples of the solvent include water; alcohols such as methanol, ethanol, isopropyl alcohol, 1-butanol, 2-butanol, sec-butyl alcohol, tert-butyl alcohol, ethylene glycol, propylene glycol, and butanediol; saturated aliphatic ether compounds such as propyl ether, isopropyl ether, butyl ether, isobutyl ether, n-amyl ether, isoamyl ether, methyl butyl ether, methyl isobutyl ether, methyl n-amyl ether, methyl isoamyl ether, ethyl propyl ether, ethyl isopropyl ether, ethyl butyl ether, ethyl isobutyl ether, ethyl n-amyl ether, and ethyl isoamyl ether; unsaturated aliphatic ether compounds such as allyl ether and ethyl allyl ether; aromatic ether compounds such as anisole, phenetole, phenyl ether, and benzyl ether; cyclic ether compounds such as tetrahydrofuran, tetrahydropyran, and dioxane; ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, and diethylene glycol monomethyl ether; ethylene glycol ether compounds such as diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, etc.; monocarboxylic acid compounds such as formic acid, acetic acid, acetic anhydride, acrylic acid, citric acid, propionic acid, butyric acid, etc.; butyl formate, amyl formate, propyl acetate, isopropyl acetate, butyl acetate, sec-butyl acetate, amyl acetate, isoamyl acetate, 2-ethylhexyl acetate, cyclohexyl acetate, butylcyclohexyl acetate, ethyl propionate, butyl propionate, amyl propionate, butyl butyrate, diethyl carbonate, diethyl oxalate, lactic acid Examples of suitable esters include organic acid ester compounds such as methyl, ethyl lactate, butyl lactate, and triethyl phosphate; ketone compounds such as acetone, ethyl ketone, propyl ketone, butyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, diisobutyl ketone, acetylacetone, diacetone alcohol, cyclohexanone, cyclopentanone, methylcyclohexanone, and cycloheptanone; dicarboxylic acid compounds such as succinic acid, glutaric acid, adipic acid, undecanedioic acid, pyruvic acid, and citraconic acid; and 1,4-dioxane, furfural, and N-methylpyrrolidone.

[0175] Among these, water and alcohol are preferred, alcohol having 1 to 4 carbon atoms is more preferred, at least one alcohol selected from the group consisting of methanol, ethanol, isopropyl alcohol, 1-butanol, 2-butanol, sec-butyl alcohol, tert-butyl alcohol, ethylene glycol, propylene glycol, and butanediol is even more preferred, and isopropyl alcohol and / or 1-butanol are particularly preferred.

[0176] The water may be pure water or may contain impurities to the same extent as tap water.

[0177] The thickness of the adhesive layer formed from the active energy ray curable adhesive is usually 0.001 to 5 μm, preferably 0.01 μm or more, and preferably 2 μm or less, and more preferably 1 μm or less. If the adhesive layer formed from the active energy ray curable adhesive is too thick, the liquid crystal cured film is likely to have a poor appearance.

[0178] [Transferred object] When preparing a laminate for use in the manufacture of a circularly polarizing plate, a polarizer or a polarizing plate may be used as the transferee. When preparing a laminate for use in the manufacture of a product other than a circularly polarizing plate (e.g., a polarizing plate with an optical compensation layer, etc.), a transferee other than a polarizer or a polarizing plate (e.g., a transferee made of the same material as the above-mentioned substrate, etc.) may be used.

[0179] [Polarizers and polarizing plates] The polarizer has a polarizing function. Examples of the polarizer include a stretched film having a dye having absorption anisotropy adsorbed thereon, a film coated with a dye having absorption anisotropy, etc. Examples of the dye having absorption anisotropy include a dichroic dye.

[0180] A stretched film having adsorbed thereon a dye having absorption anisotropy is usually produced through a process of uniaxially stretching a polyvinyl alcohol-based resin film, a process of dyeing the polyvinyl alcohol-based resin film with a dichroic dye to adsorb the dichroic dye, a process of treating the polyvinyl alcohol-based resin film having adsorbed thereon with an aqueous boric acid solution, and a process of washing with water after the treatment with the aqueous boric acid solution.

[0181] Examples of dichroic pigments include iodine and dichroic organic dyes. Examples of dichroic organic dyes include dichroic direct dyes made of disazo compounds such as CI DIRECT RED 39, and dichroic direct dyes made of compounds such as trisazo and tetrakisazo.

[0182] The thickness of the polarizer obtained by subjecting the polyvinyl alcohol-based resin film to uniaxial stretching, dyeing with a dichroic dye, treating with boric acid, washing with water and drying as described above is preferably 5 to 40 μm.

[0183] Examples of the film coated with a dye having absorption anisotropy include a film obtained by coating a composition containing a dichroic dye having liquid crystal properties, and a film obtained by coating a composition containing a dichroic dye and a polymerizable liquid crystal compound.

[0184] The film coated with the dye having absorption anisotropy is preferably thin, but if it is too thin, the strength decreases and the processability tends to be poor. The thickness of the film is usually 20 μm or less, preferably 5 μm or less, and more preferably 0.5 to 3 μm.

[0185] Specific examples of films coated with a dye having absorption anisotropy include the films described in JP-A-2012-33249 and the like.

[0186] A polarizing plate is obtained by laminating a transparent protective film on at least one surface of the polarizer via an adhesive. The transparent protective film is preferably the same transparent film as the above-mentioned substrate.

[0187] [Method of manufacturing the liquid crystal cured film] The method for producing the liquid crystal cured film of the present invention generally includes the following steps (i) and (ii). (i) A step of adding other components to a polymerizable liquid crystal compound, and further adding a solvent to prepare a liquid composition for forming a liquid crystal cured film, which contains the polymerizable liquid crystal compound. (ii) A process for producing a liquid crystal cured film by applying the liquid liquid crystal cured film-forming composition onto a substrate or onto an alignment film formed on a substrate, and polymerizing the polymerizable liquid crystal compound.

[0188] Specifically, the step (ii) can be carried out by applying a liquid crystal cured film-forming composition to a substrate surface or an alignment film surface formed on a substrate, removing a solvent in the liquid crystal cured film-forming composition, polymerizing a polymerizable liquid crystal compound in the liquid crystal cured film-forming composition, and curing the liquid crystal cured film-forming composition, as described in detail below.

[0189] Examples of a method for applying the liquid crystal cured film-forming composition to the surface of a substrate or the surface of an alignment film formed on a substrate include known methods such as coating methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and applicator methods, and printing methods such as flexography. The thickness of the liquid crystal cured film-forming composition to be applied is determined in consideration of the thickness of the liquid crystal cured film to be obtained.

[0190] Next, the solvent contained in the composition for forming a liquid crystal cured film is removed under conditions in which the polymerizable liquid crystal compound does not polymerize, thereby forming a dry coating of the composition for forming a liquid crystal cured film on the surface of the substrate or the surface of the alignment film. Examples of the method for removing the solvent include natural drying, ventilation drying, heat drying, and reduced pressure drying.

[0191] The dried film is heated or the like to cause the polymerizable liquid crystal compound contained in the dried film to have a liquid crystal orientation, and then the polymerizable liquid crystal compound is polymerized by irradiating the dried film with light while maintaining this liquid crystal orientation.

[0192] Examples of light sources for light irradiation include xenon lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, metal halide lamps, and ultraviolet lasers such as KrF and ArF, with high pressure mercury lamps, ultra-high pressure mercury lamps, and metal halide lamps being preferred.

[0193] The light to be irradiated and the light source are appropriately selected according to the type of photopolymerization initiator contained in the dried film, or the type of polymerizable liquid crystal compound (particularly, the type of polymerizable group possessed by the polymerizable liquid crystal compound), and the amount thereof. The light to be irradiated preferably includes light having a wavelength of less than 350 nm and light having a wavelength of 350 nm or more. By using such light, the polymerizable liquid crystal compound tends to be cured more sufficiently.

[0194] The light is preferably ultraviolet light, because it is easy to control the progress of the polymerization reaction and light that is widely used in this field as a polymerization device can be used. Therefore, it is preferable to select the type of polymerizable liquid crystal compound and polymerization initiator contained in the liquid crystal cured film forming composition so that it can be polymerized by ultraviolet light. When polymerizing, it is preferable to control the polymerization temperature by cooling the dried film with an appropriate cooling means together with the ultraviolet light irradiation. If the polymerizable liquid crystal compound is polymerized at a lower temperature by such cooling, the liquid crystal cured film can be appropriately produced even if a material with low heat resistance is used for the base material.

[0195] Thus, a liquid crystal cured film having liquid crystal alignment is formed on the substrate surface or the alignment film surface.

[0196] [Primer layer] A primer layer made of a transparent resin such as an epoxy resin may be provided between the liquid crystal cured film or the alignment film and the adhesive layer.

[0197] [Second adhesive layer] The second adhesive layer is formed from the same adhesive as the first adhesive layer. The second adhesive layer is formed by applying the adhesive to the surface of the liquid crystal cured film, the alignment film, or the primer layer. When the adhesive contains a solvent, the adhesive is applied to the surface of the liquid crystal cured film or the primer layer, and the solvent is removed to form the adhesive. The second adhesive layer formed from the adhesive can also be formed by applying the adhesive to the release-treated surface of the film that has been subjected to the release treatment, removing the solvent to form an adhesive layer on the release-treated surface of the film that has been subjected to the release treatment, and then laminating the film with the adhesive layer to the surface of the liquid crystal cured film or the primer layer so that the adhesive layer side becomes the lamination surface. Furthermore, the adhesion between the liquid crystal cured film or the primer layer and the second adhesive layer can be further improved by corona treatment.

[0198] The method for applying the pressure-sensitive adhesive may be the same as the method exemplified for applying the oriented polymer composition to the substrate. The method for removing the solvent from the applied pressure-sensitive adhesive may be the same as the method for removing the solvent from the oriented polymer composition.

[0199] [Embodiment 4: Display Device] The present invention may be a display device (for example, an organic EL display device, a touch panel display device, etc.) including the circular polarizer according to the third embodiment of the present invention.

[0200] [Applications of liquid crystal cured film and circular polarizing plate] The liquid crystal cured film according to the first embodiment of the present invention and the circular polarizing plate according to the third embodiment of the present invention can be used in various display devices.

[0201] A display device is a device having a display element, and includes a light-emitting element or a light-emitting device as a light source. Examples of the display device include a liquid crystal display device, an organic electroluminescence (EL) display device, an inorganic electroluminescence (EL) display device, a touch panel display device, an electron emission display device (field emission display device (FED, etc.), surface field emission display device (SED)), electronic paper (display device using electronic ink or electrophoretic element), a plasma display device, a projection type display device (grating light valve (GLV) display device, display device having digital micromirror device (DMD), etc.), and a piezoelectric ceramic display. The liquid crystal display device includes any of a transmissive liquid crystal display device, a semi-transmissive liquid crystal display device, a reflective liquid crystal display device, a direct-view liquid crystal display device, and a projection type liquid crystal display device. These display devices may be display devices that display two-dimensional images, or may be stereoscopic display devices that display three-dimensional images. In particular, a circular polarizer can be effectively used in an organic electroluminescence (EL) display device and an inorganic electroluminescence (EL) display device, and an optical compensation polarizer can be effectively used in a liquid crystal display device and a touch panel display device. EXAMPLES

[0202] The present invention will be described in more detail below with reference to examples and comparative examples. In the examples and comparative examples, "%" and "parts" are "% by mass" and "parts by mass" unless otherwise specified.

[0203] The polymer films, devices and measurement methods used in the examples are as follows: For the cycloolefin polymer (COP) film, ZF-14 manufactured by Zeon Corporation was used. The corona treatment device used was AGF-B10 manufactured by Kasuga Denki Co., Ltd. The corona treatment was carried out once using the above corona treatment device at an output of 0.3 kW and a treatment speed of 3 m / min. The polarized UV irradiation device used was a SPOT CURE SP-7 with a polarizer unit manufactured by Ushio Inc. The laser microscope used was the LEXT manufactured by Olympus Corporation. The high pressure mercury lamp used was the Uniqure VB-15201BY-A manufactured by Ushio Electric Co., Ltd. The in-plane retardation value was measured using a KOBRA-WR manufactured by Oji Scientific Instruments. The film thickness was measured using an Ellipsometer M-220 manufactured by JASCO Corporation. Infrared total reflection absorption spectra were measured using an Agilent 670-IR.

[0204] [Example 1] [Preparation of composition for forming photoalignment film] 5 parts of a photo-alignment material having the following structure and 95 parts of cyclopentanone (solvent) were mixed as components, and the resulting mixture was stirred at 80° C. for 1 hour to obtain a composition for forming a photo-alignment film (1). The following photo-alignment material was synthesized by the method described in JP 2013-33248 A.

[0205] [ka]

[0206] [Preparation of composition containing polymerizable liquid crystal compound] Polymerizable liquid crystal A having the following structure, a polyacrylate compound (leveling agent) (BYK-361N; manufactured by BYK-Chemie), and the following photopolymerization initiator were mixed as components to obtain a composition (1) containing a polymerizable liquid crystal compound.

[0207] [ka]

[0208] Polymerizable liquid crystal A was synthesized by the method described in JP 2010-31223 A. The maximum absorption wavelength λ of polymerizable liquid crystal A max (LC) was 350 nm.

[0209] The amount of the polyacrylate compound was 0.01 part based on 100 parts of the polymerizable liquid crystal A.

[0210] The following four types of photopolymerization initiators were used, and for each Example, the photopolymerization initiators shown in Table 1 were added in the amounts shown in Table 1 to 100 parts of polymerizable liquid crystal A. Table 1 also shows the maximum absorption wavelength λ(A) and maximum absorption wavelength λ(B) of each photopolymerization initiator. Irgacure OXE-03 (manufactured by BASF Japan Ltd.) ADEKA Arcles NCI-831 (manufactured by ADEKA Corporation) 2-Dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one (Irgacure 369 (Irg369); manufactured by BASF Japan Ltd.) 2,2-Dimethoxy-1,2-diphenylethan-1-one (Irgacure 651 (Irg651); manufactured by BASF Japan Ltd.).

[0211] [Manufacturing of polarizing plates] A polyvinyl alcohol film having an average degree of polymerization of about 2,400, a degree of saponification of 99.9 mol% or more, and a thickness of 75 μm was immersed in pure water at 30° C., and then immersed in an aqueous solution having a weight ratio of iodine / potassium iodide / water of 0.02 / 2 / 100 at 30° C. to perform iodine dyeing (iodine dyeing step). The polyvinyl alcohol film that had undergone the iodine dyeing step was immersed in an aqueous solution having a weight ratio of potassium iodide / boric acid / water of 12 / 5 / 100 at 56.5° C. to perform boric acid treatment (boric acid treatment step). The polyvinyl alcohol film that had undergone the boric acid treatment step was washed with pure water at 8° C., and then dried at 65° C. to obtain a polarizer (thickness 27 μm after stretching) in which iodine was adsorbed and aligned in the polyvinyl alcohol. At this time, stretching was performed in the iodine dyeing step and the boric acid treatment step. The total stretching ratio in this stretching was 5.3 times. The obtained polarizer was sandwiched between two sheets of saponified triacetyl cellulose film (KC4UYTAC 40μm, manufactured by Konica Minolta) and laminated with a water-based adhesive by nip rolls. The obtained laminate was dried at 60°C for 2 minutes while maintaining the tension at 430N / m to obtain a polarizing plate (1) having triacetyl cellulose film as a protective film on both sides. The water-based adhesive was prepared by adding 3 parts of carboxyl group-modified polyvinyl alcohol (Kuraray Co., Ltd.: Kuraray Poval KL318) and 1.5 parts of water-soluble polyamide epoxy resin (Sumika Chemtex: Sumirez Resin 650, aqueous solution with solid content concentration of 30%) to 100 parts of water.

[0212] [Production of liquid crystal cured film] N-methyl-2-pyrrolidone (NMP) was added to the composition (1) containing the above-mentioned polymerizable liquid crystal compound so that the solid content concentration was 13%, and the mixture was stirred at 80° C. for 1 hour to obtain a coating liquid.

[0213] On the other hand, a cycloolefin polymer (COP) film as a substrate was subjected to a corona treatment using a corona treatment device. Next, the above-mentioned composition for forming a photoalignment film (1) was applied to the surface of the corona-treated COP film (substrate) using a bar coater, dried at 80°C for 1 minute, and then irradiated with 100 mJ / cm using a polarized UV irradiation device. 2The alignment film was obtained by exposing the film to polarized UV light with an integrated light amount of 100 nm.

[0214] Next, the above-mentioned coating liquid was applied onto the above-mentioned alignment film using a bar coater, and after drying at 120°C for 1 minute, ultraviolet light was irradiated from the side where the coating liquid was applied using a high-pressure mercury lamp (under a nitrogen atmosphere, wavelength: 313 nm, cumulative light amount at a wavelength of 313 nm was 250 mJ / cm2). 2 or 500mJ / cm 2 ) to form a liquid crystal cured film. Also, an optical film including the liquid crystal cured film was formed. Furthermore, a polarizing plate as a transfer medium was subjected to corona treatment using a corona treatment device. The maximum absorption wavelength of the obtained liquid crystal cured film was 350 nm.

[0215] After laminating the adhesive layer to the formed optical film, the liquid crystal cured film was laminated to a polarizing plate (receiving body) that had been subjected to corona treatment via the adhesive layer. At this time, the polarizing plate was laminated so that the absorption axis of the polarizing plate and the slow axis of the liquid crystal cured film were at 45°. Thereafter, the COP film as the substrate was peeled off to obtain a circular polarizing plate (1) in which the liquid crystal cured film was transferred to the polarizing plate as the receiving body. At this time, the only layer that was transferred was the liquid crystal cured film, and the alignment film remained on the COP film as the substrate.

[0216] The in-plane retardation values ​​of the obtained circularly polarizing plate (1) for light with wavelengths of 450 nm and 650 nm were measured. As a result, the in-plane retardation values ​​were Re(450)=121 nm, Re(550)=139 nm, and Re(650)=142 nm, and the relationship of the in-plane retardation values ​​at each wavelength was as follows:

[0217] Re(450) / Re(550)=0.87 Re(650) / Re(550)=1.02 (In the formula, Re(450) represents an in-plane retardation value for light with a wavelength of 450 nm, Re(550) represents an in-plane retardation value for light with a wavelength of 550 nm, and Re(650) represents an in-plane retardation value for light with a wavelength of 650 nm.) That is, the liquid crystal cured film had the optical properties represented by the following formulas (1), (2), and (3). Note that since the in-plane retardation value of the polarizing plate was approximately 0, it did not affect the optical properties represented by formulas (1) to (3).

[0218] Re(450) / Re(550)≦1.00 …(1) 1.00≦Re(650) / Re(550) …(2) 100nm <Re(550)<160nm …(3) [Infrared total reflection absorption spectrum measurement] Among the surfaces perpendicular to the thickness direction of the above-mentioned liquid crystal cured film, a pressure-sensitive adhesive layer was attached to the surface opposite to the photo-alignment film side, and then the liquid crystal cured film was attached to a corona-treated COP film (transfer recipient) via the pressure-sensitive adhesive layer. Thereafter, the COP film as a base material was peeled off to obtain a laminate (1a) having the COP film (transfer recipient), pressure-sensitive adhesive layer, and liquid crystal cured film in this order. The infrared total reflection absorption spectrum of the obtained laminate (1a) was measured (incident angle 45°), and the obtained measurement results (in-plane bending vibration of ethylenically unsaturated bonds (1408 cm)) were obtained. -1 ) and the stretching vibration of the unsaturated bond of the aromatic ring (1504 cm -1 From the peak intensity I(2) derived from the peak intensity I(2), P' (the P value in the plane with the smaller value among the P values ​​in the two planes perpendicular to the thickness direction of the liquid crystal cured film) was calculated. The results are shown in Table 1.

[0219] In addition, a solution obtained by dissolving the polymerizable liquid crystal compound A in chloroform was dropped onto a germanium crystal and dried to obtain a thin layer of the polymerizable liquid crystal compound A. The obtained thin layer was subjected to infrared total reflection absorption spectroscopy, and the obtained measurement results (in-plane bending vibration of ethylenically unsaturated bonds (1408 cm) -1 ) peak intensity I(1) = 0.0113, stretching vibration of unsaturated bond of aromatic ring (1504 cm -1 ) from the peak intensity I(2)=0.0351), P0 (the P value of the polymerizable liquid crystal compound) was calculated to be 0.322.

[0220] [Retardation measurement during heat resistance test] Among the surfaces perpendicular to the thickness direction of the above-mentioned liquid crystal cured film, a pressure-sensitive adhesive layer (a pressure-sensitive adhesive containing an acrylic polymer) and a glass substrate were laminated in this order on the surface opposite to the photo-alignment film side, and then the COP film as the substrate was peeled off, and then the pressure-sensitive adhesive layer and the COP film (transfer recipient) subjected to corona treatment were laminated in this order to the liquid crystal cured film. As a result, a laminate (1b) having a glass substrate, a pressure-sensitive adhesive layer, a liquid crystal cured film, a pressure-sensitive adhesive layer, and a COP film (transfer recipient) in this order was obtained. The obtained laminate (1b) was placed in an oven at 85°C for 500 hours, and the in-plane retardation value was measured, and the change in the in-plane retardation value before and after the heat resistance test (change in the in-plane retardation value during the heat resistance test) was calculated.

[0221] [Examples 2 to 12] Except for changing the type and amount of the polymerization initiator to be added and the integrated amount of ultraviolet light (ultraviolet light irradiation energy at a wavelength of 313 nm) as shown in Table 1, the same operation as in Example 1 was performed to obtain compositions (2) to (12) containing a polymerizable liquid crystal compound, circular polarizing plates (2) to (12), laminates (2a) to (12a), and laminates (2b) to (12b). The maximum absorption wavelength of the obtained liquid crystal cured film was all 350 nm. In addition, in the same manner as in Example 1, the in-plane retardation value at wavelengths of 450 nm and 650 nm of the circular polarizing plate, the infrared total reflection absorption spectrum of the laminate, the in-plane retardation value during the heat resistance test of the laminate, and the change in the in-plane retardation value before and after the heat resistance test were measured and calculated. The results are shown in Table 1.

[0222] [Comparative Examples 1 and 2] Except for changing the type and amount of the polymerization initiator to be added as shown in Table 1, the same operation as in Example 1 was performed to obtain comparative compositions (1) to (2), comparative circular polarizing plates (1) to (2), and comparative laminates (1) to (2) containing a polymerizable liquid crystal compound. The maximum absorption wavelength of the obtained liquid crystal cured film was all 350 nm. In addition, in the same manner as in Example 1, the in-plane retardation value at wavelengths of 450 nm and 650 nm of the comparative circular polarizing plate, the infrared total reflection absorption spectrum of the comparative laminate, the in-plane retardation value during the heat resistance test of the comparative laminate, and the change in the in-plane retardation value before and after the heat resistance test were measured and calculated. The results are shown in Table 1.

[0223] [Reference example 1] Except for changing the type and amount of the polymerization initiator to be added as shown in Table 1, the same operation as in Example 1 was performed to obtain a reference composition (1), a reference circular polarizing plate (1), and a reference laminate (1) containing a polymerizable liquid crystal compound. The maximum absorption wavelength of the obtained liquid crystal cured film was 350 nm. In addition, in the same manner as in Example 1, the in-plane retardation value at wavelengths of 450 nm and 650 nm of the reference circular polarizing plate, the infrared total reflection absorption spectrum of the reference laminate, the in-plane retardation value during the heat resistance test of the reference laminate, and the change in the in-plane retardation value before and after the heat resistance test were measured and calculated. The results are shown in Table 1.

[0224] [Reference example 2] Except for changing the type and amount of the polymerization initiator to be added as shown in Table 1, the same operation as in Example 1 was performed to obtain a reference composition (2), a reference circular polarizing plate (2), and a reference laminate (2) containing a polymerizable liquid crystal compound. The maximum absorption wavelengths of the obtained liquid crystal cured films were all 350 nm. In addition, in the same manner as in Example 1, the in-plane retardation value at wavelengths of 450 nm and 650 nm of the reference circular polarizing plate, the infrared total reflection absorption spectrum of the reference laminate, the in-plane retardation value during the heat resistance test of the reference laminate, and the change in the in-plane retardation value before and after the heat resistance test were measured and calculated. As a result, the value of Re(450) / Re(550) (wavelength dispersion value) was 0.93, and it was found that the performance regarding the in-plane retardation of the obtained circular polarizing plate changed. Other results are shown in Table 1.

[0225] [Table 1]

[0226] [result] Comparing Examples 1 to 12 with Comparative Examples 1 and 2, it was found that in the comparative examples, the change in the in-plane retardation value during the heat resistance test was −10 nm (Comparative Example 1) or −15 nm (Comparative Example 2), and the in-plane retardation value changed (decreased) significantly, whereas in Examples 1 to 12, the change in the in-plane retardation value during the heat resistance test was −2 to −4 nm, and the change in the in-plane retardation value was small.

[0227] That is, it was found that the liquid crystal cured films having a (1-P' / P0) x 100 value of 73 or more (75 to 93 in Examples 1 to 12) showed a smaller change in retardation value during the heat resistance test than the liquid crystal cured films having a (1-P' / P0) x 100 value of less than 73 (72 in Comparative Example 1 and 64 in Comparative Example 2), and therefore could reduce the amount of decrease in retardation value when exposed to a high-temperature environment. [Industrial Applicability]

[0228] The liquid crystal cured film obtained by polymerizing and curing the polymerizable liquid crystal compound of the present invention and the optical film containing the liquid crystal cured film can reduce the amount of decrease in in-plane retardation when exposed to a high-temperature environment. The liquid crystal cured film and the optical film of the present invention can be widely used in displays such as organic electroluminescence (EL) displays and touch panel displays.

Claims

1. A liquid crystal cured film obtained by polymerizing a polymerizable liquid crystal compound, The liquid crystal cured film has a maximum absorption wavelength in the range of 300 nm or more and 380 nm or less, Satisfies formula (Y), (1-P' / P0)×100≧73…(Y) (In the formula, P′ represents the P value on the smaller of the two P values ​​on the surfaces perpendicular to the thickness direction of the liquid crystal cured film. P0 represents the P value of the polymerizable liquid crystal compound. The P value is expressed as I(1) / I(2). I(1) represents the peak intensity due to the in-plane bending vibration of an ethylenically unsaturated bond as determined by infrared total reflection absorption spectroscopy, and I(2) represents the peak intensity due to the stretching vibration of an unsaturated bond in an aromatic ring as determined by infrared total reflection absorption spectroscopy. The liquid crystal cured film further contains a photopolymerization initiator composition, The photopolymerization initiator composition contains a photopolymerization initiator having an oxime structure in the molecule and an α-acetophenone compound, The photopolymerization initiator having an oxime structure in the molecule has two or more absorption maxima at a wavelength of 300 nm or more, The amount of the photopolymerization initiator having an oxime structure in the molecule is 10 / 3 to 12.5 / 3 times the amount of the α-acetophenone compound.

2. The liquid crystal cured film according to claim 1 , which satisfies formula (3). 100nm<Re(550)<160nm...(3) (In the formula, Re(550) represents an in-plane retardation value for light having a wavelength of 550 nm.)

3. The liquid crystal cured film according to claim 1 or 2, which satisfies formula (1) and formula (2). Re(450) / Re(550)≦1.00…(1) 1.00≦Re(650) / Re(550)…(2) (In the formula, Re(450) represents an in-plane retardation value for light having a wavelength of 450 nm, Re(550) represents an in-plane retardation value for light having a wavelength of 550 nm, and Re(650) represents an in-plane retardation value for light having a wavelength of 650 nm.)

4. The maximum absorption wavelength λ of the polymerizable liquid crystal compound max (LC) 300nm≦λ max (LC)≦380nm The liquid crystal cured film according to any one of claims 1 to 3, which satisfies the above.

5. The photopolymerization initiator composition has a maximum absorption wavelength λ(A) and a maximum absorption wavelength λ(B), These maximum absorption wavelengths λ(A) and λ(B) are λ(A)<λ(B) The liquid crystal cured film according to any one of claims 1 to 4, which satisfies the above.

6. The maximum absorption wavelength of the photopolymerization initiator composition and the maximum absorption wavelength λ of the polymerizable liquid crystal compound max (LC) 20 nm < λ(B) - λ max (LC) or 20nm<λ max (LC)-λ(A) The liquid crystal cured film according to claim 5 , which satisfies the above.

7. The liquid crystal cured film according to any one of claims 1 to 6, comprising 1 to 20 parts by mass of the photopolymerization initiator composition relative to 100 parts by mass of the polymerizable liquid crystal compound.

8. The liquid crystal cured film according to any one of claims 1 to 7, which is obtained by curing a composition containing the polymerizable liquid crystal compound and the photopolymerization initiator composition.

9. The photopolymerization initiator composition has a maximum absorption wavelength λ(A) and a maximum absorption wavelength λ(B), These maximum absorption wavelengths λ(A) and λ(B) are λ(A)<λ(B) The liquid crystal cured film according to claim 8 .

10. The maximum absorption wavelength of the photopolymerization initiator composition and the maximum absorption wavelength λ of the polymerizable liquid crystal compound max (LC) 20 nm < λ(B) - λ max (LC) or 20nm<λ max (LC)-λ(A) The liquid crystal cured film according to claim 9 .

11. The liquid crystal cured film according to any one of claims 8 to 10, comprising 1 to 20 parts by mass of the photopolymerization initiator composition relative to 100 parts by mass of the polymerizable liquid crystal compound.

12. An optical film comprising the liquid crystal cured film according to any one of claims 1 to 11.

13. A circularly polarizing plate comprising the liquid crystal cured film according to any one of claims 1 to 11 and a polarizing plate.

14. An organic electroluminescence display device comprising the liquid crystal cured film according to any one of claims 1 to 11.

15. A touch panel display device comprising the liquid crystal cured film according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Transflective liquid crystal display device

    JP2007241071A

  • Optical compensation sheet, polarizing plate and liquid crystal display device

    JP2007279421A

  • Optical compensation film, its forming method, polarizer, and liquid crystal display

    JP2009098664A

  • Optical film

    JP2010152217A

  • Method of manufacturing biaxial retardation film

    JP2011002556A